Plan de mejoramiento de la calidad del servicio al cliente en base a la metodología Servqual en la Empresa Municipal de Agua Potable y Alcantarillado de Guaranda, provincia Bolívar, año 2023. - Gavilanes Muñoz, Ana del Rocío (2024)
In this work, the quality of the service of the Municipal Drinking Water and Sewerage Company from Guaranda is measured with the Servqual methodology. The Servqual model measures service quality through customer preferences and perceptions based on five dimensions: reliability, sensitivity, security, empathy, and material value. About the investigation, the main problem was analyzed, is the lack of knowledge about the level of quality of the expert assistance service and the fulfillment of the proposed objectives. The Thesis deals with the design and development of a “Customer Service Quality Improvement Plan” in the EMAPAG Company. The main approach is based on the SEVQUAL methodology, recognized for its to assess and improve the quality of services. This methodology is used as a conceptual framework to analyze the expectations and perceptions of customers in relation to several aspects of the service provided by the drinking water and service company. Finally, this investigation aspires to propose a comprehensive set of recommendations and concrete actions for the Customer Service Quality Improvement Plan, with the purpose of raising the quality standards perceived by users, By implementing the plan based on the SERVQUAL methodology the Municipal Drinking Water and Sewerage Company from Guaranda could not only increase customers satisfaction, but also strengthen its relationship with the community and ensure efficiency and effectiveness in the provision of its services in a Dynamic and demanding context.